Pós-tratamento de efluente doméstico de reator anaeróbio utilizando filtração rápida para fins de reúso: estudo físico químico e toxicológico - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
This work evaluates the use of a double and triple filtration pilot unit, consisting of an upflow gravel filter, a fast downstream sand filter and a downward filter composed of activated carbon and / or zeolite (clinoptilolite) for post - effluent treatment from anaerobic reactor. As a preliminary step to double and triple filtration, coagulation / settling used, with the objective of assisting the removal of total suspended solids (TSS) and Turbidity, which reduced the filter overhead. In this stage, concentrations of 20 were used; 50 and 80 mg / L of ferric chloride, to check the possibility of reducing the use of coagulant. After the treatment tests, the efficiency of the system was evaluated by means of filtration careers and, subsequently, characterized by physical-chemical and microbiological tests. In all treatments carried out in the pilot unit, the concentration of suspended solids remained <1.0 mg / L, which reflected reductions greater than 99% in turbidity. The triple filtration with activated carbon (TFac) removed the chemical oxygen demand (COD), biological oxygen demand (BOD) and dissolved organic carbon (COD) above 95%. Triple filtration with clinoptilolite (TFc) was more efficient in removing total nitrogen and ammonia nitrogen above 99%. The metal ion concentrations were significantly lower in the triple filtration treatment with activated carbon Cu (99%), Mn (94%), Cd (99%), Cr (98%) and Ni (98) and in the triple filtration treatment with clinoptilolite Al (91%), Cu (97%), Cd (99%), Cr (99%) and Ni (98%). Ammoniacal nitrogen concentrations in relation to anaerobic reactor effluent treatments (69.0 mg / L); double filtration (44.0 mg / L) and TFca (46.6 mg / L) and TFc (0.33 mg / L) can be a limiting factor for the development of embryos and larvae during ecotoxicity tests, since only triple filtration with clinoptilolite showed no toxicity. The treatments with the presence of the oxidizer peracetic acid (PAA) and calcium hypochlorite showed high disinfection of the effluent, and the activity of fecal indicators (E. coli and total coliforms) not verified. Considering the possibilities of reuse, the post-treated anaerobic reactor effluent by double and triple filtration can be used in landscape irrigation, fire fighting, toilet flushing, creation and maintenance of water bodies, reuse in industrial cooling systems, food crops in general and indirect drinking. According to the results of the filtration careers, approximately 91% of the filtered effluent can be reused after treatment. A study carried out with determination of the parameters of Consolidation Ordinance No. 5, of September 28, 2017, annexes 7 and 10, showed that the post-treated effluent through triple filtration using a mixed activated carbon / clinoptilolite filter meets the criteria of drinking water.
Keywords: Efluente doméstico; Dupla Filtração; Tripla Filtração; Ácido Peracético; Cloro livre.; Domestic Effluent; Double Filtration; Triple Filtration; Peracetic acid; Free chlorine; CNPQ::CIENCIAS EXATAS E DA TERRA::QUIMICA